Produtos técnicos e tecnológicos na pós-graduação em psicologia: complexidade institucional e disputas simbólicas no campo científico - Miguel, Juan Rodrigo Reys (Universidade Federal de São Carlos, 2025)
This dissertation examines the challenges and potential for academic legitimation of Technical and Technological Products (TTPs) in graduate programs, focusing on the Graduate Program in Psychology at the Federal University of São Carlos (PPGPsi/UFSCar). Grounded in New Institutionalism (Meyer & Rowan; DiMaggio & Powell; Scott) and Pierre Bourdieu’s reflexive sociology, the study treats TTPs as institutional phenomena shaped by coercive, normative, and cognitive pressures, as well as symbolic disputes over the definition of valid scientific knowledge. The research employs a qualitative methodology through a multi-level document analysis (macro, meso, and micro) of CAPES reports and PPGPsi institutional documents from 2001 to 2025, supported by Natural Language Processing (NLP) tools for data systematization. A distinctive feature is the researcher's situated perspective as an Administrative Education Technician (TAE) within the program, providing reflexive insight into the tensions between administrative and academic logics. Findings reveal a "legitimation performance" marked by a decoupling between institutional discourse favoring social impact and evaluative practices that prioritize traditional bibliometric metrics. While TTPs have gained formal and regulatory recognition (pragmatic and moral legitimacy), they remain cognitively marginalized within the academic habitus. To address this, the dissertation proposes a tripartite intervention for institutional recoupling: (1) a draft for institutional norms integrating TTPs into degree requirements; (2) a graduate course on technical production; and (3) a Reference Guide for TTP development. The work offers practical and critical contributions to the debates on assessment, dialogic outreach, and the public role of science against agnotology and disinformation.
Technical and technological products in psychology graduate studies: institutional complexity and symbolic disputes in the scientific field
Keywords: Novo institucionalismo; Pierre Bourdieu; Produtos técnicos e tecnológicos; Avaliação da pós-graduação; Psicologia; Agnotologia; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::SOCIOLOGIA::FUNDAMENTOS DA SOCIOLOGIA::TEORIA SOCIOLOGICA; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; 4. Educação de Qualidade; 16. Paz, Justiça e Instituições Eficazes